Civil Society, Demokrasi dan Demokratisasi - Wan Asrida; Auradian Marta; Sofyan Hadi (Nakhoda: Jurnal Ilmu Pemerintahan, 2021)
This study aims to provide an explanation of the relationship between civil society, democracy, and democratization and to explain the contribution of civil society to democratization. The method used in this study is a literature study or literature study. Sources of information from this study are from books and journals of research results which are analyzed with relevant theories. The results of this study indicate that there is a close conceptual and practical relationship between civil society, democracy, and democratization. Civil society has both positive and negative implication in democratization. The positive implications of civil society for democratization are when it is able to play a role in bringing changes from authoritarianism to democratic consolidation by taking on the role of balancing state power, defending public interests, and being able to influence the state policy agenda for mutual prosperity. Civil society also has a negative side if it is dominated by ethnocentrism, radicals, and power oriented.